Marketing channels of chili: players, levels, and segmentations - Joko Mariyono (Universitas Hayam Wuruk Perbanas, 2019)
Chili production is an essential commodity in Indonesia, and the marketing issues frequently disrupt the economy. This paper aims to analyze the distribution channel of chili and formulate a suitable policy to overcome the marketing problems. A market survey was qualitatively conducted at a producer, intermediary, wholesaler, and retailer levels. The results were descriptively presented using tables and figures. The analysis shows that the marketing channel of chili in Indonesia was long and complicated. Many players were starting at the village level to the provincial level. Segmented markets were based on the types of chili, which were categorized as local and hybrid cultivars. Farmers selected the marketing channels because of business circumstance and their farm location. Distance and gentleman agreement with traders limited farmers to select the marketing channel. Thus, the government is strongly recommended to provide a unique vegetable market such as an agribusiness terminal close to the center of production. This action will shorten the marketing chain such that both producers and consumers gain the benefits. The role of the private sector will be crucial in order to keep healthy agribusiness.